Digital Maternal Health Education: Exploring the Potential of Mobile Applications for Anemia Prevention - Widiastuti, Dhias; Dhita Aulia Octaviani; Rafika Fajrin (Postgraduate Program , Poltekkes Kemenkes Semarang, 2025)
Anemia during pregnancy remains a major public health concern in Indonesia, with a prevalence of 37.1% reported in 2020. Despite ongoing iron supplementation programs, mild anemia continues to occur, potentially leading to maternal and neonatal complications. Mobile health applications offer innovative opportunities to enhance maternal knowledge and self-monitoring practices. This study aimed to develop and evaluate a prototype of a mobile-based anemia education application for pregnant women. A pre-experimental study involving 30 pregnant women aged 31–43 years at Puskesmas Ngesrep, Semarang, was conducted. Hemoglobin (Hb) levels were measured and participants were guided to use the application, which included features such as anemia information, Hb input, automatic anemia classification, and prevention tips. Results showed that 90% of respondents had normal Hb levels, while 10% experienced mild anemia. Feedback on the application was overwhelmingly positive: 100% of respondents agreed the application was easy to use, informative, visually appealing, and helpful in understanding anemia, with willingness to use it again. These findings align with previous studies emphasizing the role of mobile health tools in maternal education. The study concludes that the application has strong potential for further development, particularly in content enhancement and interactive features. The prototype reached Technology Readiness Level (TRL) 4–5, validating the system in a limited setting. This work contributes to advancing digital maternal health solutions in Indonesia. Keywords: pregnant women; anemia; mobile application; health education; maternal literacy